Pengaruh Financial Socialization dan Sikap Keuangan terhadap Penggunaan Paylater pada Gen Z Kota Palu - Aulia, Sofiah Dwi; Fattah, Vitayanti; Muslimin, Muslimin; Rianty, Cici (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The development of financial technology (FinTech) has presented digital credit services such as Paylater, which are increasingly popular among Generation Z. This study analyzes the influence of financial socialization and financial attitudes on the use of Paylater among Gen Z in Palu City. Data were collected through an online survey of 100 respondents selected by purposive sampling method and analyzed using structural equation modeling (SEM) with SmartPLS. The results showed that financial socialization and financial attitude have a positive and significant effect on the use of Paylater, with financial attitude having a stronger influence. Individuals with adequate financial understanding and a healthy financial attitude tend to use this service more wisely. These findings emphasize the importance of financial education in encouraging wiser use of Paylater among Gen Z.